PERANCANGAN DAN PEMBUATAN APLIKASI MOBILE TOURISM INFORMATION KOTA BATAM BERBASIS ANDROID - Rico Adrial (JURNAL ILMIAH INFORMATIKA, 2018)
Batam city is one of the destinations for vacation. Its maked batam often visited by tourists. Strategic location became another reason, which is directly adjacent to Singapore and Malaysia. Based on the target of the government, who want to realize Batam as a city of tourism, so in the city of Batam there are various kinds of vacation spots such as beach with rides game, babana boat, etc. In addition to the holiday spot, Batam have various culinary and souvenirs. However, the location of tourism information is still very difficult to find. The information is only found in personal blogs that are rarely updated. The number of application development using a smartphone, then designed an application that can help tourists find the location they want while in Batam. This application is called mobile tourism information. Its contains tourist attractions, culinary, and souvenirs in Batam